Mindfulness and MBCT-vision (mindfulness-based cognitive therapy modified for visual symptoms) for visual snow syndrome: a therapeutic perspective - Wong, Sui H.; Wingrove, Janet (Frontiers in Neurology, 2025)
Visual snow syndrome (VSS) is a neurological disorder characterized by intrusive visual symptoms and associated with dysregulation in brain networks, including the Salience Network, Default Mode Network, and thalamocortical circuits. This perspective paper examines the application of mindfulness-based cognitive therapy modified for visual symptoms (MBCT-vision) as an intervention for VSS. Drawing on clinical experience, our recent open-label study, and ongoing randomized controlled trial, we propose that VSS symptoms may perpetuate through attentional mechanisms, including heightened vigilance and threat attribution. We outline how mindfulness practices in MBCT-vision address these processes by enhancing attentional flexibility, increasing metacognitive awareness, and fostering a non-reactive stance toward symptoms. The group-based format of MBCT-vision provides additional therapeutic benefits through shared understanding and validation. We discuss potential neuroplastic mechanisms underlying observed improvements, particularly involving the Default Mode Network. This paper advances the understanding of mindfulness mechanisms in VSS and provides a foundation for developing comprehensive, evidence-based approaches that integrate neurobiological insights with person-centered therapeutic strategies for this challenging condition.